Helsepersonells erfaringer og tanker om bruk av frivillige i palliativ omsorg - Skaar, Ragnhild; Fensli, Marthe M. F.; Flateland, Sylvi M.; Söderhamn, Ulrika (Nordisk tidsskrift for helseforskning, 2017)
Health care personnel’s experiences and thoughts on the use of volunteers in palliative care in a social perspective The government of Norway is planning for the municipalities’ health care resources, including volunteering. The purpose of this study was to shed light on the experiences and thoughts of a group of health care personnel on the use of volunteers in palliative care in the community health care services, and to discuss the findings in a social perspective. Individual interviews were conducted with seven nurses and three nursing assistants. Using a qualitative content analysis three categories emerged: "The importance of organization, clarification and responsibility," "Qualifications" and "Different types of tasks," with the overarching theme: “Close monitoring and good clarification of roles can contribute to suitable volunteers functioning as an appropriate supplement for patients in palliative care in the community health care services”. The informants stated that trained health care personnel must perform the nursing tasks in palliative care while volunteers can be a positive supplement for the patient.